Remote Sensing And Geospatial Applications For Water Catchment Mapping And Assessment. - Md. Said, Md. Azlin; Bawahidi, Khaled; Affan, Muzailin (2005)
Identifying and mapping water catchment features that occur in mostly forest areas from aerial photography is a challenging task, but the use of remotely sensed data and data processing techniques can improve the process of providing preliminary data for modeling land use and land cover changes and assessment their impact on the catchemnt.